Effect of Alkali Metal Nitrates on the Ru/C-catalyzed Ring Hydrogenation of m-Xylylenediamine to 1,3-Cyclohexanebis(methylamine) - Kim, Young Jin; Lee, Jae Hyeok; Widyaya, Vania Tanda; Kim, Hoon Sik; Lee, Hyunjoo (WILEY-V C H VERLAG GMBH, 2014)
Ru/C-catalyzed hydrogenation of m-xylylene diamine into 1,3-cyclohexanebis(methylamine)' was greatly accelerated by the presence of LiNO3, NaNO2, or NaNO3. It was found that the effect of the nitrate salt was significantly affected by the size of cation. The promoting effect of the nitrate salt increased with the decrease of the cation size: LiNO3 similar to NaNO3 > KNO3 > CsNO3 >> [1-butyl-3-methylimidazolium]NO3. XRD analysis of the recovered catalysts after the hydrogenation reactions showed that LiNO3 and NaNO3 were completely transformed into LiOH and NaOH, respectively, along with the evolution of NH3, while KNO3 and CsNO3 remained unchanged.
Keywords: RUTHENIUM